The Paston Letters, A.D. 1422-1509. Volume 4 (of 6) : New Complete Library Edition - Gairdner, James, 1828-1912 (Salt Lake City, UT : Project Gutenberg, 2012)
"The Paston Letters, A.D. 1422-1509. Volume 4 (of 6)" by James Gairdner is a historical collection edited in 1904. This volume presents authentic correspondence between members of Norfolk's Paston family and their associates during the tumultuous Wars of the Roses and early Tudor period. These letters offer intimate glimpses into medieval English life, revealing family struggles, political intrigue, and social dynamics. The collection also captures language in transition, documenting the shift from Late Middle English to Early Modern English during the Great Vowel Shift, making it invaluable to both historians and linguists. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Paston_Letters
Release date is 2012-10-16
E-text prepared by Louise Hope, Chris Curnow, and the Online Distributed Proofreading Team (http://www.pgdp.net) from page images generously made available by Internet Archive/Canadian Libraries (http://archive.org/details/toronto)
Keywords: England -- Social life and customs -- 1066-1485 -- Sources; English letters; Paston family -- Correspondence; Social history -- Medieval, 500-1500 -- Sources; Letter writing -- History -- To 1500 -- Sources; Great Britain -- History -- Lancaster and York, 1399-1485 -- Sources; Great Britain -- History -- Henry VII, 1485-1509 -- Sources